1934
DOI: 10.1002/ange.19340473704
|View full text |Cite
|
Sign up to set email alerts
|

Der Quecksilbergehalt der menschlichen Ausscheidungen und des menschlichen Blutes

Abstract: liei3 sich leicht auf Grund der Konzentrationen der Elementgruppen As-Ge-Ga, P-As und Platinmetalle Ireffen.Auch bei t e c h n i s c h e n E i s e n -u n d S t a h la r t e n lafit sich feststellen, welche Werke z. T i e r e u a d P f 1 a n z e n nehmen mit der Nahrung chemischen Fabriken verwenden als A u sg a n g s s t o f f e f u r d i e H e r s t e l l u n g d e ra no r g a n i s c h e n unld o r g a n i s c h e n C h e m i k a -1 i e n in-und auslandische Rohstoffe. Man ist meist in der Lage, aus den klei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1938
1938
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Germany in the first half of this century, Alfred Stock was a strong advocate of extreme safety precautions in the use and handling of the metal (17)(18)(19)(20)(21). Much of his research into the study of the hazards of Hg was prompted by his own experience as indicated in the quotation at the beginning of this section (17; translation taken from 12, Chap.…”
Section: Historical Perspectives Of Mercurymentioning
confidence: 99%
“…Germany in the first half of this century, Alfred Stock was a strong advocate of extreme safety precautions in the use and handling of the metal (17)(18)(19)(20)(21). Much of his research into the study of the hazards of Hg was prompted by his own experience as indicated in the quotation at the beginning of this section (17; translation taken from 12, Chap.…”
Section: Historical Perspectives Of Mercurymentioning
confidence: 99%